Physiological differences and implications to reproductive management of Bos taurus and Bos indicus cattle in a tropical environment - Sartori, R.; Bastos, M. R. [UNESP]; Baruselli, P. S.; Gimenes, L. U.; Ereno, R. L. [UNESP]; Barros, C. M. [UNESP]; Lucy, M. C.; Pate, J. L.; Smith, M. F.; Spencer, T. E. (Nottingham Univ Press, 2010)
In the current review the main fundamental biological differences in reproductive function between Bos taurus and Bos indicus cattle are discussed. Breed differences regarding puberty, estrous cycle patterns, estrous behavior, acquisition of ovulatory capacity, ovarian structures and reproductive hormones are presented. The main physiological differences that Bos indicus cattle present relative to Bos taurus cattle include: delayed age at puberty; higher circulating concentrations of hormones such as estradiol, progesterone, insulin and IGF-I, despite having smaller ovulatory follicle size and corpora lutea; greater population of small follicles and smaller size of the dominant follicle at deviation; and greater sensitivity of follicles to gonadotropins. Knowledge of the differences between Bos indicus and Bos taurus breeds help explain different management procedures and responses to hormonal treatments associated with artificial insemination, ovarian superstimulation, and in vivo and in vitro embryo production.